The Effectiveness of Price Regulation - Meyer, Robert A.; Leland, Hayne E. (The Review of Economics and Statistics, 1980)
That it is easier to measure the costs of price regulation than the benefits is evident in the conflicting results of studies made to determine welfare gains. An econometric study based on a simple theory of demand by customer class concludes that: (1) the effectiveness of regulation across states is irregular, which suggests that state regulatory agencies confront firms with highly variable political climates and may serve customers with an uneven quality of benefits; (2) the pattern of cross-subsidization of prices that penalized residential customers in 1969 was gone or shifted to favor residential customers by 1974; (3) a more-detailed re-evaluation of the presumed benefits and costs of nonuniform pricing may be warranted; and (4) welfare improvements appear to be possible. The dominant question that emerges is how to explain what underlying forces contribute to the substantial state-to-state and between-customer variations in regulatory impact. 13 references, 6 tables.